STK24 expression is modulated by DNA copy number/methylation in lung adenocarcinoma and predicts poor survival. (20th March 2018) - Huang, Ningyu; Lin, Wenbo; Shi, Xiuyu; Tao, Tao
Aim: To explore the independent prognostic value of STK24 expression in terms of overall survival and recurrence-free survival and the potential mechanisms of its dysregulation in non-small-cell lung adenocarcinoma.Patients & methods: Data were from the Cancer Genome Atlas-lung adenocarcinoma.Results: Increased STK24 expression was an independent prognostic indicator of unfavorable overall survival (Hazard ratio: 1.478; 95% CI: 1.149–1.901; p < 0.002) and recurrence-free survival (Hazard ratio: 1.855; 95% CI: 1.399–2.458; p < 0.001). DNA amplification was associated with significantly upregulated STK24 expression. There was a weak negative correlation between STK24 expression and its DNA methylation (Pearson's r = -0.32).Conclusion: Aberrant STK24 expression was an independent prognostic indicator in lung adenocarcinoma patients. Its dysregulation was associated with its DNA copy number alteration and methylation.